How can the use of blog software facilitate the writing process of English language learners? - Arslan, Recep Şahin; Kızıl, Aysel Şahin (My University, 2010)
Blog use may offer instructors a helpful tool for teaching writing at the tertiary level in Teaching English as a Foreign Language (TEFL) classrooms. This article reports on a quasi-experimental study regarding the effect of blogcentered writing instruction on students’ writing performance. Fifty intermediate English students at a Turkish university participated in the study. The control group (n ¼ 23) received in-class process-oriented writing instruction and the experimental group (n ¼ 27) integrated blogs into their writing processes by using a blog software. Based on the analyses of students’ written work, the findings suggest that blog-integrated writing instruction might have resulted in a greater improvement in students’ writing performance than merely in-class writing instruction. The study therefore supports the conclusion that English as a Foreign Language practitioners’ use of blog software has potential to promote more effective writing instruction.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Blog; Process oriented writing instruction; Blogging